Design of a Height Crest Profile of a GFRP Composite Roofing Sheets. (2017) - Setyanto, Djoko
Abstract: The height crest profile of metal roofing sheets is the common option for Japanese factory buildings in Indonesia. The metal roofing sheets are installed on the supporting bars/ purlins with mechanical locking system without any holes. Based on this system, the paper describes how to design a similar height crest profile of roofing sheets made of a GFRP composite material that is produced in a continuous laminating machine. It was found six types of height crest profiles that are met to the profile that is installed on the purlins by mechanical locking system. The six roofing sheets structures are simulated with uniform static forces on the two local areas of valley of roofing sheets by using finite element method. Based on both stress and deflection distribution of the six finite element models of roofing sheet structure, the selected type of crest profile is the trapezoidal. The roofing sheets of GFRP material consist of three trapezoidal type crests and two valleys. It was produced in a continuous laminating machine by using seven until twenty rows of mold. A row/ set of mold consist of three parts, one bottom part and two upper parts.